2013
DOI: 10.1007/s00508-013-0329-z
|View full text |Cite|
|
Sign up to set email alerts
|

Female and male victims of violence in an urban emergency room—prevalence, sociodemographic characteristics, alcohol intake, and injury patterns

Abstract: To conclude, victims of violence seek for help in emergency rooms daily. Alcohol consumption is the main factor for violent behavior. Public health programs to prevent alcohol related violence and therefore, alcohol-attributable injuries have to be implemented. Addressing the need to enhance the awareness of the health professionals has to be an imperative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…(2009), had been subjected in a public place, meaning that this violence was probably not inflicted by an intimate partner, while 40% of the women exposed to violence had been exposed in a domestic setting and a higher percentage may thus have been the victims of violence inflicted by an intimate partner. This results taken together with other research exploring gender differences substance abuse and violence [56] , [57] , [58] , indicates that violence against young women often differs from that against young men, frequently occurring at other places and possibly in other situations, with consequences that are more serious for the health of the women. Young men and women do not face equal risks of exposure to violence.…”
Section: Understanding the Association Between Self-reported Exposuresupporting
confidence: 65%
“…(2009), had been subjected in a public place, meaning that this violence was probably not inflicted by an intimate partner, while 40% of the women exposed to violence had been exposed in a domestic setting and a higher percentage may thus have been the victims of violence inflicted by an intimate partner. This results taken together with other research exploring gender differences substance abuse and violence [56] , [57] , [58] , indicates that violence against young women often differs from that against young men, frequently occurring at other places and possibly in other situations, with consequences that are more serious for the health of the women. Young men and women do not face equal risks of exposure to violence.…”
Section: Understanding the Association Between Self-reported Exposuresupporting
confidence: 65%
“…Scholars generally consider IPV among men as less severe than IPV against women, whereby the common difference in physical strength between women and men is thought to result in no severe IPV-related injuries to male victims [24]. A Portuguese study found only minor injuries, such as bruises and abrasions on male victims, and sharp weapons were present in only 2.8 % of cases, while an Austrian Emergency Department-based study found no male victims of IPV at all [25,26]. In the United States, female IPV victims were two times more likely to experience abuse with a knife or a gun compared with male victims [27].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 80% of the victims were under the age of 40 and one-third of the patients had consumed alcohol. 20 In a study examining emergency clinic admission rates of 1,441 substance-use patients within last 6 months, no violence was reported in 46.8%, partner violence was reported in 17.3%, nonpartner violence was reported in 20.2%, and both partner and nonpartner violence was reported in 15.7% of the patients. 21 In our study, mean age and rates of violence among women were similar and 17.8% of the victims had a history of alcohol use.…”
Section: Discussionmentioning
confidence: 99%